Maize for sale - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Money is the true friend. Economic practice, morality and trust among the Iganga maize traders in Uganda By P Sørensen, Apad Lit verlag Münster, Germany, 2000. 227 pp. ISBN 3 8258 4393 9 Euro 20.90